Homestay Service for Tourist Satisfaction in Rural Areas - Anil Ghimire (Centre For Tourism Planning and Development, 2023)
Homestay services are less well-known than hotel services for tourism. However, homestay is an important aspect of tourism, not just as lodging but as a travel attraction. This study examines the influence of the homestay experience on tourist satisfaction and its significance within the context of the tourism industry. The homestay experience was examined using 244 survey questionnaires. This study demonstrated that homestay experience affects destination satisfaction and behavioural intention. Homestay services are a destination attraction because tourists want to experience the destination's traditional culture. To increase destination satisfaction, include local cultural activities in the accommodation service. Therefore, this study has the potential to improve our knowledge of the hospitality sector broadly.